2020
DOI: 10.1002/adfm.202002549
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Patterning, Transfer Printing and Post‐Assembly of Multiscale Adhesion‐Free Metallic Structures for Nanogap Device Applications

Abstract: Patterning of metallic nanogaps with ultrasmall gap size on arbitrary substrates is of great importance for various applications in nanoelectronics, nanoplasmonics, and flexible optoelectronics. Common lithographic approaches suffer from limited resolution in defining ultrasmall nanogaps and restrictive available substrates for flexible and stretchable devices. In this work, a process portfolio to overcome the above limitations is proposed, enabling the fabrication of multiscale metallic nanogaps with reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…101 Furthermore, by introducing a self-assembled monolayer to engineer the surface energy of the substrate, the adhesiveness of the Al film outside outline template is significantly decreased to implement the selective peeling process, various plasmonics Al nanostructures with sub-20 nm feature sizes were successfully achieved by SPL approach, suggesting the tremendous potential and fabricating ability of the technology. [102][103][104] To optical properties and applications of artificial plasmonic metal atoms, the hybridization model for the plasmon response of complex nanostructures provides a simple effective guideline. 105 As shown in Fig.…”
Section: Figure 4 the Schematic Illustration Of General Growth Models Of Metal Filmsmentioning
confidence: 99%
“…101 Furthermore, by introducing a self-assembled monolayer to engineer the surface energy of the substrate, the adhesiveness of the Al film outside outline template is significantly decreased to implement the selective peeling process, various plasmonics Al nanostructures with sub-20 nm feature sizes were successfully achieved by SPL approach, suggesting the tremendous potential and fabricating ability of the technology. [102][103][104] To optical properties and applications of artificial plasmonic metal atoms, the hybridization model for the plasmon response of complex nanostructures provides a simple effective guideline. 105 As shown in Fig.…”
Section: Figure 4 the Schematic Illustration Of General Growth Models Of Metal Filmsmentioning
confidence: 99%
“…[ 5 ] Furthermore, in a recent work from H. Duan's group, the transfer printing process has been improved to create 5 nm wide nanogaps between two metal electrodes. [ 6 ] Thus, the ability to transfer printing nanoscale metal objects has been fully demonstrated. Despite that, the compatible materials with the transfer printing process are rather limited except for metals, which hinder the development of flexible electronic/optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…[143] A number of variations to the SPL procedure have been reported. [144][145][146][147][148] For instance, instead of using a negative resist, it is possible to directly create nano-trenches in a deposited metal film by FIB milling before selectively removing the metal outside of the trenches by peeling, see Figure 14. [142] In the case of a silicon substrate, it has been shown that slight over-milling of the unwanted metal causes a thin layer of silicon atoms to be sputtered onto the side walls of the retained metal, which serves to protect the retained metal from damage during the subsequent peeling step.…”
Section: Peeling-based Methodsmentioning
confidence: 99%